The First Record of Dina sivricensis (Hirudinea: Erpobdellidae) from Duhok Province, Iraq, Based on COI Barcoding - Kachel, Hamid; Omer, Imad; Sadeeq, Barwar; Ali, Farhad; Saglam, Naim (ABADER (Adiyaman Bilimsel Arastirmalar Dernegi), 2026)
Erpobdellid leeches are important freshwater predators that frequently pose major taxonomic problems due to their high morphological similarity. Dina Blanchard, 1892, is a genus distributed exclusively throughout Eurasia and has been differentiated from related genera by its mid-body annulation. This study presents the first molecular evidence for Dina sivricensis from Duhok Province, Iraq. Recently recorded as a new species from Türkiye, D. sivricensis is distinguished by its small cylindrical body and unique reproductive organs, including a small spherical atrium and an ellipsoidal atrial cornea. Species identification was verified using cytochrome c oxidase subunit I (COI) barcoding. The sequence obtained in this study (PZ144795) showed 95%–97% similarity to reference sequences of D. sivricensis, which were deposited under accession numbers MH013409 and MG949122 in GenBank. This study has recorded D. sivricensis from Iraq, thereby extending its known geographic range and contributing to the recorded diversity of erpobdellids in Iraq. © 2026 ABADER (Adiyaman Bilimsel Arastirmalar Dernegi). All rights reserved.
COI Barkodlama Temelinde Dina sivricensis (Hirudinea: Erpobdellidae)'in Irak'ın Duhok İlinden İlk Kaydı
Keywords: Biodiversity; Genetic Marker; Leech; Molecular Identification; Phylogenetic Analysis